EVALUATION OF THE PROHIBITION OF BEGGING POLICY IN MEDAN CITY - Surya Waldi Surya; Tunggul Sihombing (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study focuses on evaluating the Prohibition of Beggars Policy in Medan City, implemented by the Medan City Social Service as stipulated in Regional Regulation No. 6 of 2003 concerning the prohibition of homeless people and beggars and the practice of prostitutes. The purpose of this study was to find out and describe in detail the evaluation of the prohibition of beggars policy in Medan City. This study uses a descriptive research method with a qualitative approach. Through this research it can be seen that the evaluation of the ban on beggars policy in Medan City has not run optimally. The problem is that facilities and infrastructure, enforcement related to sanctions which are an important aspect in evaluating the ban on beggars policy in Medan City, are not in line with the policy objectives, thus hindering the evaluation in achieving the goals of the ban on beggars policy in Medan City.